Power of Magnetic - Van Zanten, Leonard (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The theme here is about magnetism and what is produced by it, looking at the sun, the earth, as well as the atom, and in general. It also shows magnetic for its nature of - with or without pressure to limit the velocity of the relative movement upon atoms and molecules. Our interpretation for temperature as well as other factors related to the stars are updated to include such factors as we apparently are unaware of. And it goes into a summary view of gravity in how it relates to the power of magnetic. And the unique nature of magnetic how it is in physics as well as mentally portrayed. One might say; "A look inside the mind of the author."